2014
DOI: 10.1002/ana.24200
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐surface central nervous system autoantibodies: Clinical relevance and emerging paradigms

Abstract: The recent discovery of several potentially pathogenic autoantibodies has helped identify patients with clinically distinctive central nervous system diseases that appear to benefit from immunotherapy. The associated autoantibodies are directed against the extracellular domains of cell-surface–expressed neuronal or glial proteins such as LGI1, N-methyl-D-aspartate receptor, and aquaporin-4. The original descriptions of the associated clinical syndromes were phenotypically well circumscribed. However, as availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
149
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 166 publications
(170 citation statements)
references
References 164 publications
(263 reference statements)
3
149
0
10
Order By: Relevance
“…In this study, we evaluated the rituximab responsiveness 1 month after the standard rituximab treatment, based tocilizumab group, at the time of monthly rituximab therapy initiation in the additional rituximab group, and at 1 month after the last cycle of weekly rituximab therapy in the observation group First-line = at initiation of first-line immunotherapies; RTX = at initiation of standardregimen weekly rituximab; RTX 1 mo = at 1 month from the initiation of weekly rituximab therapy; 1 mo = at 1 month from the baseline time points; 2 mo = at 2 months from the baseline time points; last FU = at the last clinical follow-up point on the fact that timely control of disease is essential to improve outcomes in AE [35], and that early discrimination of drug responsiveness is fundamental in the considering further treatment options. In this study, clinical improvement from standard-regimen rituximab was reported in 85/176 (48.3 %) patients [29/55 (52.7 %) for the anti-NMDA-R encephalitis subgroup].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated the rituximab responsiveness 1 month after the standard rituximab treatment, based tocilizumab group, at the time of monthly rituximab therapy initiation in the additional rituximab group, and at 1 month after the last cycle of weekly rituximab therapy in the observation group First-line = at initiation of first-line immunotherapies; RTX = at initiation of standardregimen weekly rituximab; RTX 1 mo = at 1 month from the initiation of weekly rituximab therapy; 1 mo = at 1 month from the baseline time points; 2 mo = at 2 months from the baseline time points; last FU = at the last clinical follow-up point on the fact that timely control of disease is essential to improve outcomes in AE [35], and that early discrimination of drug responsiveness is fundamental in the considering further treatment options. In this study, clinical improvement from standard-regimen rituximab was reported in 85/176 (48.3 %) patients [29/55 (52.7 %) for the anti-NMDA-R encephalitis subgroup].…”
Section: Discussionmentioning
confidence: 99%
“…Thus the frequency of the entire range of PNDs and neuronal antibodies in SCLC has not been determined systematically. Furthermore, with the recent discovery of a new category of disorder mediated by autoantibodies against neuronal cell surface proteins such as NMDA receptor and LGI1, 8 it is important to determine whether these antibodies are present in SCLC PNDs.…”
mentioning
confidence: 99%
“…In adults, autoantibodies to essential neuronal proteins such as the N ‐methyl‐ d ‐aspartate receptor (NMDAR) and the voltage gated potassium channel (VGKC)‐complex antigen, leucine rich glioma inactivated 1 (leucine rich glioma inactivated 1 (LGI1), are now widely recognized as an important treatable cause of encephalitis 1, 2. Patients present with memory loss, confusion, and seizures in limbic encephalitis with predominantly LGI1 antibodies3, 4 and neuropsychiatric features, movement, and autonomic symptoms in NMDAR‐Ab (antibody) encephalitis 5, 6.…”
mentioning
confidence: 99%